STUDY ON THE SUSTAINABILITY OF THE USE OF ANTIMICROBIAL (AMU) AND ANTIMICROBIAL RESISTANCE (AMR) IN MARINE FISH FARMING IN THE BAY - Syaripuddin; Bethsy J Pattiasina; Shelly M Pattipeiluhu (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: Use of antibiotics and chemicals substances were done to prevent bacterial attacks especially by Vibrio sp, which if used excessively will cause bacterial resistance. Another problem that arises is the risk of damage to the surrounding environment of fish farming and human health, therefore the use of these substances must be effective and efficient. The research aims to determine the antimicrobial inhibition during the handling of cage-cultured fish diseases and to determine the level of resistance to antimicrobial substances (Antimicrobial Resistance/AMR) to obtain recommendations for the sustainability of antimicrobial use. Disk diffusion test method with antibiotics Oxytetracycline, Enrofloxacin, and Tetracycline in paper disc form was used in the inhibition test. Bacterial identification used biochemical tests with bacterial culture media (TCBS) also biochemical tests using the API 20E kit. The results show that the inhibitory power of using the three types of antibiotics is able to provide sensitive and intermediate responses to Vibrio sp bacteria. Sensitivity inhibition in white snapper, trevally, grouper, and humpback grouper with oxytetracycline antibiotics all at 60%, enrofloxacin antibiotics respectively 80%, 100%, 100%, and 80%; and tetracycline antibiotics respectively 60%, 100%, 60%, and 80%. Intermediate inhibition with the same group of fishes with oxytetracycline antibiotics all at 40%, enrofloxacin antibiotic in all fish 0%, except in humpback grouper 20% and tetracycline antibiotics respectively 40%, 0%, 40%, and 20%. Thus, it can be concluded that the use of oxytetracycline, enrofloxacin, and tetracycline antibiotics can still be recommended for the management of diseases in aquaculture. For common bacteria, two types of bacteria Vibrio parahaemolyticus and Vibrio alginolyticus have been found. Keywords: Resistance, Vibrio spp, antibiotics, fish farming